Digital Transformation In Public Services: Opportunities and Challenges - Doddy Ramdhan (Peneliti.net, 2023)
Digital transformation has become an increasingly relevant topic in the context of public services. Information and communication technology provides opportunities to increase the efficiency, effectiveness and quality of public services. However, digital transformation also presents challenges in terms of access gaps, data security, and paradigm shifts in organizational culture. This study aims to identify opportunities and challenges from digital transformation in public services. In a literature review, the author collects literature from various sources and conducts a thematic analysis to identify key issues related to digital transformation in public services. The results of the analysis show that digital transformation provides opportunities in terms of increasing the efficiency, effectiveness and quality of public services. Technologies such as big data, cloud computing, and artificial intelligence can be used to optimize decision making, increase citizen participation, and reduce operational costs. However, digital transformation also presents challenges in terms of access gaps, especially for people who are less skilled in using technology, data security and privacy, as well as paradigm shifts in organizational culture. This study concludes that digital transformation in public services offers great opportunities for the government to improve service quality and efficiency. However, the challenges faced in its implementation must be managed properly. The role of government, especially in terms of regulation and investment, is very important to ensure the success of digital transformation in public services